Analysing the effect of government policy intervention on cross-border freight transportation flows: the Belt and Road perspective. Issue 2 (29th November 2019) - Kundu, Tanmoy; Sheu, Jiuh-Biing
Abstract : This work proposes a two-stage transport flow model to analyse the dynamics associated with the cross-border freight transport flows induced by the cross-governmental policy intervention. The stage-1 framework is modeled using a game profile based on cross-governmental interaction, followed by the stage-2 conducted using the spatial interaction approach to examine its induced effect on the transport flows. The case of the Belt and Road initiative is illustrated to demonstrate the validity and applicability of the proposed model using Chinese oil transport data. Analytical results suggest strategies of policy development and transit route choice decision for the policymakers and the practitioners in the Belt and Road network strategic context.